A curious case of a lost capsule: A rare case of small bowel diaphragm disease - Motij Kumar Dalai; Meghraj AnIngle; Vikas Pandey; Shamshersingh Gajendra Chauhan; Yogesh Bairwa; Rohit Wagh (Society of Gastrointestinal Intervention, 2023)
Diaphragm disease (DD) is a rare condition that is associated with the use of nonsteroidal anti-inflammatory drugs. It is characterized by multiple diaphragm-like septa that cause a narrowing of the small bowel lumen. The diagnosis of this disorder can be challenging due to its rarity and its non-specific symptoms, which often suggest other, more probable diseases. We report the case of a 16-year-old boy who presented with iron-deficiency anemia that did not respond to iron supplementation. Despite undergoing endoscopy and computed tomography (CT) enterography, the cause of his condition could not be identified. Capsule endoscopy was attempted, but due to technical difficulties, images could not be obtained. Two years later, the patient's symptoms persisted, prompting further investigation. CT enterography revealed a foreign body in the distal ileum, which was identified as the previously administered capsule. Diagnostic laparoscopy with intraoperative endoscopy was performed to retrieve the capsule. This procedure also revealed multiple short-segment strictures causing luminal narrowing and ulcerations. These were confirmed by histopathology to be lesions associated with DD.